Fight zone with points of the shotokan karate female competition - Marques Junior, Nelson Kautzner (2014)
The aimof the study was to determine the fight zone with point during the female kumite of competition. This study used a quantitative research for identify the fight zone with point (ippon or waza-ari) or not during the female kumite of competition. Were selected on the Internet several championship of kumite of the JKA and of the ITKF. The study detected a high probability of point in the zone 7 and in the zone 2. The study determined that the most points at the corner occurred when the karateka practiced the attack in fight zone. Kruskal-Wallis ANOVA verified significant difference between the fight zone with points, H (10) = 29,49, p = 0,001. The Mann Whitney U test detected significant difference between the zone 5 with waza-ari versus all the zone. The greatest number of points in the fight zone was in agreement with the size of the fight zone. The central zone or zone 5 has 6x6 m, during the female kumite occurred more points, total of 68 waza-aris and 5 ippons. The study on the fight zone with points of the female kumite permits that the karateka has knowledge about the combat zones and guides the karateka before, during and after the female kumite. However, more studies should be done to confirm these findings.